POTRET PENGADAAN JASA KONSTRUKSI SECARA ELEKTRONIK DI SULAWESI TENGAH - Asnudin, Andi (MEKTEK, 2012)
Electronic procurement is expected to be done in an efficient and effective, transparent, accountable and provide equal opportunities for all contractors to be the winning bidder. Descriptive analysis method used in this study, by using contractors who attended the auction on LPSE UNTAD as respondents.The results showed that various problems faced by portrait contractors, among others: the ability of the limited human resources, hardware and software readiness is low, poor data base systems, supporting data is incomplete.The resulting recommendations, among others, (1) an increase in capacity building to all relevant parties, (2) the availability of infrastructure to support electronic procurement system, and (3) allow all parties can access the documents to see the complete contractors that has been in an effort to load up the procurement process transparent and competitive so as to provide equal opportunities for contractors (4) continuously shaped discussion forum involving all stakeholders.